The impact of local social spending on the political dissatisfaction of economically deprived individuals — Evidence from Dutch municipalities - Hummler, Teresa; Vierus, Paul (Frontiers in Political Science, 2025)
Previous research demonstrates that local conditions are highly visible and proximate for citizens and thus have a distinct impact on political attitude formation. However, we still lack knowledge of the interplay of the local and the individual level. In this study, we examine how a specific group (economically deprived individuals) responds to local social spending in the formation of political dissatisfaction. Research at the national level has provided contradictory findings concerning the influence of social policy measures. To shed new light on this interrelationship, we investigate the extent to which the individual link between economic hardship and political dissatisfaction is moderated by the level of local social spending. To empirically gauge this, we use panel data from the Netherlands merged with municipality-level data on social spending. Results from multilevel regressions reveal that the positive relationship between economic hardship and political dissatisfaction is mitigated in municipalities with higher levels of local social spending, suggesting a resource effect. Changes in the economic situation over time play a crucial role in this regard since the connection between economic hardship and political dissatisfaction is particularly pronounced for individuals in constant economic hardship.